2019
DOI: 10.1084/jem.20182010
|View full text |Cite
|
Sign up to set email alerts
|

Tcf1 and Lef1 are required for the immunosuppressive function of regulatory T cells

Abstract: Tcf1 and Lef1 have versatile functions in regulating T cell development and differentiation, but intrinsic requirements for these factors in regulatory T (T reg) cells remain to be unequivocally defined. Specific ablation of Tcf1 and Lef1 in T reg cells resulted in spontaneous multi-organ autoimmunity that became more evident with age. Tcf1/Lef1-deficient T regs showed reduced protection against experimentally induced colitis, indicative of diminished immuno-suppressive capacity. Transcriptomic analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 68 publications
5
72
0
Order By: Relevance
“…2B and 2C, left panel). In consistent with the previous study (Xing et al, 2019), these results indicated that TCF-1 deficiency leads to enhanced colitis. However, these severe colitis symptoms are not only originated from dysbiosis since the intestinal inflammation is associated with multiple complicated factors.…”
Section: Lettersupporting
confidence: 93%
“…2B and 2C, left panel). In consistent with the previous study (Xing et al, 2019), these results indicated that TCF-1 deficiency leads to enhanced colitis. However, these severe colitis symptoms are not only originated from dysbiosis since the intestinal inflammation is associated with multiple complicated factors.…”
Section: Lettersupporting
confidence: 93%
“…When grouped by resting, primed/activated, and activated Treg subsets, cell states had differential expression of known lymphoid-associated and activated genes. Resting Tregs (C1) have high expression of lymphoid-tissue homing receptors (Ccr7 and S1pr1) and Treg-establishing transcriptional regulators (Lef1 [Xing et al, 2019], Satb1 [Kitagawa et al, 2017], and Klf2 [Pabbisetty et al, 2016]) and low-activation marker expression (Ctla4, Icos, Tnfrsf1b, and Tnfrsf4) ( Figs 3D and S7A), suggesting that they either have not yet undergone TCR-mediated activation or have a central memory-like phenotype.…”
Section: Molecular Characterization Of Resting Primed and Activatedmentioning
confidence: 99%
“…Cell states identified by clustering could be grouped into resting, primed/activated, and activated Treg populations based on known lymphoid-associated and activated gene expression. Resting Tregs (C1) have high expression of lymphoid-tissue homing receptors (Ccr7, S1pr1, Sell) and Treg-establishing 5 transcriptional regulators (Lef1 (22), Satb1(23) and Klf2 (24)) and low activation marker expression (Ctla4, Icos, Tnfrsf1b, Tnfrsf4) ( Fig. 2D, Fig.…”
Section: Molecular Characterization Of Resting Primed and Activatedmentioning
confidence: 99%